Interventions promoting physical activity among adults and children in the six Gulf Cooperation Council countries: protocol for a systematic review. Issue 8 (20th August 2020) - Pearson, Fiona; Huangfu, Peijue; Abu-Hijleh, Farah M; Awad, Susanne F; Abu-Raddad, Laith J; Critchley, Julia A
Abstract : Introduction: Prevalence of overweight, obesity and diabetes are high and rising across the Gulf Cooperation Council (GCC) countries (Oman, Bahrain, Kuwait, Qatar, Saudi Arabia and the United Arab Emirates). In parallel, physical activity (PA) levels are low relative to international standards. PA aids weight control and reduces risk of non-communicable diseases including diabetes and cardiovascular disease. It is likely interventions developed elsewhere will not translate to GCC countries due to unique environmental, social and cultural factors. This protocol is for a systematic review assessing the efficacy of interventions promoting PA within GCC countries among generally healthy adults and children. The primary outcome of interest is change in objectively measured or self-reported PA levels, the secondary outcomes of interest are changes in anthropometry or chronic disease risk factors (eg, blood pressure). Interventions will be compared with no intervention or those of differing PA intensity or duration. The relationships between PA change and the following will be assessed: intervention intensity or duration, season in which intervention occurs, sex, age, nationality and sustainability over time. Methods and analysis: A systematic search strategy will identify indexed publications on the efficacy of interventions promoting PA. Randomised controlled trials and quasi-experimental studies recruiting predominantly healthy children and adults will be included. Studies of exercise rehabilitation will be excluded. Medline, Embase, Cinahl, Cochrane Library, SportDiscus, Web of Science, Index Medicus for the Eastern Mediterranean Region and Qscience will be searched. Clinical trial registries including the International Clinical Trials Registry Platform, the Iranian Registry of Clinical Trials and ClinicalTrials.gov will be searched for ongoing and unpublished studies. Searches will be ran from database inception until 1 May 2020 and be supplemented by checking references of key articles. Two reviewers will independently screen identified citations then full texts using prespecified inclusion and exclusion criteria. Piloted data extraction forms will be used in duplicate. Inconsistencies in screening or data extraction will be resolved by a third investigator or study author contact. Risk of bias will be independently assessed by two reviewers using validated tools. A narrative summary of findings will be produced supplemented with meta-analyses and exploration of heterogeneity as appropriate. Ethics and Dissemination: The review aims to strengthen the findings of the primary studies it incorporates and explore the impact of setting. It will synthesise existing published aggregate patient data. If publications or data with ethical concerns are identified, they will be excluded from the review. Results of the systematic review will be published in full and authors will engage directly with research audiences and key stakeholders to share findings. PROSPERO registration number: 131817.